Współczesny nauczyciel - wybrane problemy i wyzwania zawodowego funkcjonowania = The contemporary teacher - sellected requirements and challenges of professional functioning - Olczak, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is a theoretical analysis of the changing role of the contemporary teacher. The author discusses the required competences, the possible causes of the decline in the teacher`s authority, as well as the changes sought/possible/necessary in the teacher`s education and position. One can accept the existing situation and preserve the omnipresent role model of the teacher (as the depositary of knowledge, power, and the manager of the learning process and pupils` activity), but the developmental and social consequences of this state of affairs will be borne by pupils, deprived at school of the opportunity to develop the contemporarily required competences and to acquire important skills.`
Keywords: nauczyciele; relacje; demokracja; zmiana; teacher; relations; democracy; change